2011
DOI: 10.1007/s12325-011-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diagnosed Adult Immune Thrombocytopenia in the United Kingdom

Abstract: Introduction: Data regarding the prevalence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
0
30
1
Order By: Relevance
“…However, our estimate of prevalence was higher probably because we included patients over 64 years old and included patients without private insurance. Our annual prevalence estimates are higher than the adult estimates from Bennett, et al (18) possibly due to the differences between cases identified from administrative data compared to electronic medical records or differences between the USA and UK.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…However, our estimate of prevalence was higher probably because we included patients over 64 years old and included patients without private insurance. Our annual prevalence estimates are higher than the adult estimates from Bennett, et al (18) possibly due to the differences between cases identified from administrative data compared to electronic medical records or differences between the USA and UK.…”
Section: Discussioncontrasting
confidence: 83%
“…(26) The progressively increasing prevalence among older people and a greater prevalence of men relative to women among people 60 years and older is notable. Segal and Powe(17) and Bennett, et al(18) also described increased prevalence among older adults. The increased prevalence of ITP among older people is consistent with previous reports that the annual incidence of ITP is greatest among the oldest age cohorts;(5;13;27) in one of these reports the increased incidence among older males was also described.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Armed with their validated definition, the authors then set out to determine the frequency of ITP without restrictions, something that had previously only been done using databases of managed health care plans, limited to age groups or by point-prevalence questionnaires [18][19][20][21]. The authors found that the average annual prevalence of ITP was 8.1 per 100,000 children and 12.1 per 100,000 adults.…”
mentioning
confidence: 99%